Bioethical Boundaries, Critiques of Current Paradigms, and the Importance of Transparency. Issue 1 (28th December 2021) - Parker, J Clint
Abstract: This issue of The Journal of Medicine and Philosophy is dedicated to topics in clinical ethics with essays addressing clinician participation in state sponsored execution, duties to decrease ecological footprints in medicine, the concept of caring and its relationship to conscientious refusal, the dilemmas involved in dual use research, a philosophical and practical critique of principlism, conundrums that arise when applying surrogate decision-making models to patients with moderate intellectual disabilities, the phenomenology of chronic disease, and ethical concerns surrounding the use of artificial intelligence in medicine. Throughout the issue, the themes of conceptual and moral boundaries in bioethics, critiques of current clinical ethics paradigms, and the importance of transparency are prominent.